(3GdJbjIs - (3GdCfUGQj, eQJVi GdCfUGQj, eQJVi Hf eMeO Cejf GdORahdj GdCfUGQj, J (B1281(3g` (B1864(3es ((3cQHdGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3GdJbjI cGdJbGI GSe dCJbi jJbj hGdJGA HOd Yf GdhGh ceG aj (B.. (3hGdeQGO HgG GdJMaX Yf VQQs
(3BNQgG (B:s
(3BNQgG(B: (3abdJ jG CejQ GdeDefjf EfG hGddg dG CHQFJc bGd EPG hGddg jbJdc hjUdc bGd bdJ GUHQ GUHQ aEf PGc aj Gddg bdjd bGd (B.. (3aEPG Jchf eYjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 201s
(3GdPQjYI, L (B4: 295s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds